PENGARUH UKURAN PERUSAHAAN, RISIKO PERUSAHAAN, INTENSITAS MODAL DAN STRUKTUR KEPEMILIKAN TERHADAP PENERAPAN KONSERVATISME AKUNTANSI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Periode 2019 -2021) - Jesica, Jesica; Manik, Ester Tiorida Br; Rasyikah, Filza; Rahmi, Namira Ufrida; Lubis, Putri Kemala Dewi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This research investigates how accounting conservatism in BEI manufacturing companies from 2019 to 2021 is impacted by size, risk, capital intensity and ownership structure. Over 3 years, 78 companies were selected using the purposive sampling method. This 2019-2021 research was carried out using SPSS, and multiple linear regression, descriptive tests, classical assumptions, multiple linear regression, F test, T test, and coefficient of determination. This research also found that company size, risk, capital intensity and ownership structure have an impact on accounting conservatism in manufacturing companies on the IDX.